2021
DOI: 10.1007/s00383-020-04848-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for stricturing Crohn’s disease in childhood: a systematic review

Abstract: Purpose Childhood stricturing Crohn’s disease (CD) has significant morbidity. Interventions including resection, stricturoplasty and endoscopic balloon dilatation (EBD) are often required. Optimal intervention modality and timing, and use of adjuvant medical therapies, remains unclear. We aim to review the therapies used in paediatric stricturing CD. Methods A systematic review in accordance with PRISMA was performed (PROSPERO: CRD42020164464). Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
2
0
3
Order By: Relevance
“…• Debe realizarse una endoscopia cuando se sospecha pouchitis. • En estenosis únicas, mayores de 4 cm o múltiples, no se recomienda el uso de dilatación con balón por el mayor riesgo de complicaciones y menor tasa de éxito (28) . • Antes de realizar la dilatación endoscópica se recomienda caracterizar el número de estenosis, la naturaleza de las mismas (inflamatorias o fibróticas) y la longitud utilizando enteroresonancia (28) .…”
Section: No Pueden Ser Pasadasunclassified
See 2 more Smart Citations
“…• Debe realizarse una endoscopia cuando se sospecha pouchitis. • En estenosis únicas, mayores de 4 cm o múltiples, no se recomienda el uso de dilatación con balón por el mayor riesgo de complicaciones y menor tasa de éxito (28) . • Antes de realizar la dilatación endoscópica se recomienda caracterizar el número de estenosis, la naturaleza de las mismas (inflamatorias o fibróticas) y la longitud utilizando enteroresonancia (28) .…”
Section: No Pueden Ser Pasadasunclassified
“…• En estenosis únicas, mayores de 4 cm o múltiples, no se recomienda el uso de dilatación con balón por el mayor riesgo de complicaciones y menor tasa de éxito (28) . • Antes de realizar la dilatación endoscópica se recomienda caracterizar el número de estenosis, la naturaleza de las mismas (inflamatorias o fibróticas) y la longitud utilizando enteroresonancia (28) . • Si hay presencia de fístulas o abscesos cerca del sitio de estenosis, se recomienda no realizar dilatación por el riesgo de perforación (28) .…”
Section: No Pueden Ser Pasadasunclassified
See 1 more Smart Citation
“…A recent systematic review of population-based studies reported the highest prevalence in Germany (322 per 100000) and Canada (319 per 100000). The incidence of pediatric CD ranges from 2.5–11.4 per 100000 worldwide[ 3 , 4 ]. Common symptoms of CD in children include fever, abdominal pain, bloody or mucopurulent chronic diarrhea, anemia, poor growth, and signs of intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms include perianal anomalies, such as abscesses or fistulas, and extraintestinal manifestations like arthritis, erythema nodosum, and uveitis. Notably, despite available treatment strategies for reducing the progressive inflammatory process of the disease, approximately 25% of children with CD develop stricturing CD (SCD) that requires intervention[ 2 , 4 , 5 ]. Approximately 10% of patients present with complicated disease at diagnosis.…”
Section: Introductionmentioning
confidence: 99%